The effect of Poland’s integration with the EU on changes in the volume of production and agricultural income - Poczta, Walenty; Czubak, Wawrzyniec (Publishing House of the Wrocław University of Economics, 2009)
In this paper the data of Economic Accounts for Agriculture – EAA were used. Methodology of calculations is accordance with the calculations of production output and income in Eurostat. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 379-388